Geometry Effect Investigation on a Conical Chamber with Porous Media Boundary Condition Using Computational Fluid Dynamic (CFD) Technique - Yazid Bindar (Institute for Research and Community Services, Institut Teknologi Bandung, 2009)
The present study is an attempt to introduce a method for optimizing the geometry of a unit process. The comprehensive unit process performances are generated by a CFD engine. The CFD engine can simulate the unit process performances at whatever conditions. Both design geometry and operating variables were used on the CFD simulation. The burden on a simplified process was taken out from CFD simulation. A complex geometry of a unit process is represented by a secondary reformer. A secondary reformer has a conical chamber as a space to undergo a combustion reaction before entering a catalyst bed. This complexity is added by the boundary on a porous solid surface as the top surface of the catalyst bed. The conical angle affects the flow pattern inside the conical chamber having a porous solid surface as its base. The conical angle above 65° results the disappearing of the recirculation flow. The inlet distance from the porous solid surface also can exhibit different characteristics of recirculation flow. The closer the distance to the porous solid surface, the stronger the recirculation is. The inlet velocity values have no significant effect on the flow pattern. The introduction of a solid volume inside the geometry creates distortion in the flow pattern. In the application, the inserted solid volume is equivalent to a burner. It means that the use of the burner inherently produces some problems of the flow distribution.